Polymorphism of MDR1, MTHFR, GSTM1, GSTT1 genes and predisposition to development of childhood acute leukemia - Savitskaya, Tatsiana (Journal of the Belarusian State University. Ecology, 2023)
The role of genetic polymorphisms in the development of cancer is still under active study, but already today accumulated data show its importance in medicine. Research in this area will not only help to better understand the mechanisms of carcinogenesis, but also to identify risk groups for each nosology and to monitor these groups for early detection of cancer. When searching for genetic markers of oncohematological diseases, polymorphisms of genes involved in xenobiotic biotransformation systems were investigated. Molecular genetic methods were used: polymerase chain reaction and restriction analysis. The study identifies for the first time the frequencies of MDR1, MTHFR, GSTM1, GSTT genotypes in Belarusian children. Analysis of associations of polymorphic variants of MDR1 C3435T gene with the risk of acute leukemia revealed that heterozygous individuals with the «wild-type» MDR1 C3435T allele have a reduced risk of acute leukemia development, while homozygous carriers of 2 mutant MDR1 T3435T alleles have a significant risk for both acute lymphoblastic leukemia (ALL) and acute myeloblastic leukemia (AML) (p = 0.01 and p = 0.02, respectively). Analysis of associations of GSTT1 gene polymorphic variants revealed that children with the «not 0» genotype had an almost 6-fold increased risk of acute leukemia compared to patients with the «0» genotype, and a significantly higher risk of AML (p = 0.003). No statistically significant associations of MDR1 G2677T, MTHFR C677T, and GSTM1 polymorphisms with the risk of acute leukemia were found, indicating that none of these genotypes studied was a predisposition factor for this disease. Our research has shown the importance of genetic polymorphism as a factor determining susceptibility to acute leukemia. Further study of gene polymorphism and its association with various diseases will make it possible to characterize genetic features characteristic of the Belarusian population.